2010
DOI: 10.1089/rej.2009.0895
|View full text |Cite
|
Sign up to set email alerts
|

Intake of a Milk-Based Wolfberry Formulation Enhances the Immune Response of Young-Adult and Aged Mice

Abstract: Aging is associated with alterations of immune responses. Wolfberry, a popular Chinese functional ingredient, is prized for its anti-aging properties; however, little is known about the immunological effect of wolfberry intake. The purpose of this study was to examine the effect of dietary intake of a milk-based formulation of wolfberry, named Lacto-Wolfberry, on in vivo and ex vivo parameters of adaptive immunity in young-adult and aged mice. Over 44 days, young-adult (2 months) and aged (21 months) C57BL/6J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Rats were immunized as described by Vidal et al 26 The T cell-dependent humoral response (antigen-specific antibody production) was measured after immunization of rats with KLH, an innocuous protein isolate that generates a strong T cell-mediated antibody response and has been used extensively in animals. All rats were immunized on day 15 of the study with a subcutaneous injection of 250 lg of KLH emulsified in 1% Imject Alum.…”
Section: Immunization Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…Rats were immunized as described by Vidal et al 26 The T cell-dependent humoral response (antigen-specific antibody production) was measured after immunization of rats with KLH, an innocuous protein isolate that generates a strong T cell-mediated antibody response and has been used extensively in animals. All rats were immunized on day 15 of the study with a subcutaneous injection of 250 lg of KLH emulsified in 1% Imject Alum.…”
Section: Immunization Protocolmentioning
confidence: 99%
“…The response was calculated as the difference in ear thickness of the rats before and after challenge with a recall antigen. DTH response assay was performed according to the method of Vidal et al 26 In brief, on day 22 of the study (i.e., 7 days after KLH immunization), the thickness of the ears was measured with a micrometer, and immediately thereafter the DTH response was elicited by intradermal injection of KLH (20 lL of 1lg/mL in phosphate-buffered saline Blood sampling and hematologic index/biochemical parameter assays…”
Section: Dth Response Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…A specially formulated wolfberry product called Lacto-Wolfberry (LWB), 8 which is made by homogenizing wolfberries in skimmed milk, has been shown to greatly enhance bioavailability of zeaxanthin (18). Recent studies have shown that dietary supplementation with wolfberry can enhance immune responses in both animals and humans (19,20). Furthermore, LWB supplementation (13.7 g/d) was reported to increase specific antibody response to the influenza vaccine in healthy free-living elderly individuals (21).…”
Section: Introductionmentioning
confidence: 99%